Reduced Biventricular Volumes and Myocardial Dysfunction Long-term After Pediatric Heart Transplantation Assessed by CMR. Issue 12 (December 2019) - Latus, Heiner; Hachmann, Pauline; Voges, Inga; Mueller, Simon; Gummel, Kerstin; Reich, Bettina; Sarikouch, Samir; Peters, Brigitte; Mazhari, Nona; Behnke-Hall, Kachina; Jux, Christian; Apitz, Christian; et al.
Abstract : Background: Long-term cardiac remodeling after heart transplantation (HT) in children has been insufficiently characterized. The aim of our study was to evaluate ventricular size in HT patients using cardiovascular magnetic resonance (CMR) imaging, to find underlying factors related to potentially abnormal cardiac dimensions and to study its impact on functional class and ventricular function. Methods: Seventy-five pediatric HT recipients (age 14.0 ± 4.2 y) were assessed by using CMR 11.2 ± 5.4 years after HT. Right ventricular (RV) and left ventricular (LV) volumes and mass were derived from short-axis cine images and myocardial strain/strain rate was assessed using myocardial feature tracking technique. Results were compared with a healthy reference population (n = 79, age 13.7 ± 3.7 y). Results: LV end-diastolic ventricular volumes were smaller (64 ± 12 versus 84 ± 12 mL/m 2 ; P < 0.001) while mass-to-volume ratio (0.86 ± 0.18 versus 0.65 ± 0.11; P < 0.001) and heart rate (92 ± 14 versus 78 ± 13 beats/min; P < 0.001) were higher in HT patients. LV-ejection fraction (EF) was preserved (66% ± 8% versus 64% ± 6%; P = 0.18) but RV-EF (58 ± 7 versus 62% ± 4%, P = 0.004), LV systolic longitudinal strain (−12 ± 6 versus −15% ± 5%; P = 0.05), diastolic strain rate (1.2 ± 0.6 versus 1.5 ± 0.6 1/s; P = 0.03), and intra and interventricular synchrony were lower in the HT group. Smaller LV dimensions were primarily related to longer follow-up time since HT (β = −0.38; P < 0.001) and were associated with worse functional class and impaired ventricular systolic and diastolic performance. Conclusions: Cardiac remodeling after pediatric HT is characterized by reduced biventricular size and increased mass-to-volume ratio. These adverse changes evolve gradually and are associated with impaired functional class and ventricular dysfunction suggesting chronic maladaptive processes affecting allograft health. Abstract : Supplemental Digital Content is available in the text.